KEBERWACANAAN VISUAL : MENCERMATI PERAN PEREMPUAN DALAM IKLAN - Kweldju, Siusana (Institute of Research and Community Outreach - Petra Christian University, 2001)
In everyday life%2C we are overwhelmed by visual information. The written information has more limited scope%2C particularly in educational milieu. Visual information is mostly practiced by ads which also exploit women for embellishment resulting in gender bias. Visual discourse needs to studying to educate ourselves in perceiving and interpreting ads at higher level. Abstract in Bahasa Indonesia : Dalam kehidupan sehari-hari informasi visual lebih banyak menerpa kita. Informasi tulis lebih kecil lingkupnya%2C terutama hanya di lingkungan sekolah saja. Informasi visual ini banyak dimanfaatkan oleh iklan%2C dan iklan juga banyak mengeksploitasi perempuan untuk menyemarakkannya%2C sehingga terjadi bias gender. Keberwacanaan visual perlu dipelajari supaya kita lebih cerdas dalam memahami dan menginterpretasi iklan. gender%2C advertisement%2C visual discourse.